On blame and reciprocity: Theory and experiments (2017)
The theory of reciprocity is predicated on the assumption that people are willing to reward kind acts and to punish unkind ones. This assumption raises the question of what kindness is. In this paper, we offer a novel definition of kindness based on a notion of blame. This notion states that for player j to judge whether or not player i is kind to him, player j has to put himself in the position of player i, and ask if he would act in a manner that is worse than what he believes player i does. If player j would act in a worse manner than player i, then we say that player j does not blame player i. If, however, player j would be nicer than player i, then we say that player j blames player i. We believe this notion is a natural, intuitive and empirically functional way to explain the motives of people engaging in reciprocal behavior. After developing the conceptual framework, we test this concept by using data from two laboratory experiments and find significant support for the theory. © 2017 Elsevier Inc.